Arsenic accumulation and reproductive toxicity in freshwater snail (Pomacea canaliculata) - Xiaoyang Bi; Zhifei Shi; Dongqin Li; Wenhui Zhan; Zhixiong Wang; Huashou Li; Benliang Zhao; Guikui Chen (Ecotoxicology and Environmental Safety)
This study aimed to investigate the tissue-specific accumulation patterns of arsenic (As) and the potential toxicological effects of As on the oviposition of a globally distributed aquatic invertebrate, the apple snail (Pomacea canaliculata). An eight-compartment physiologically based pharmacokinetic (PBPK) model was utilized to simulate the distribution and depuration kinetics of arsenite and arsenate in the snails. Modeling and biotransformation suggested that intestine-stomach was the main uptake site for As and plays an important role in maintaining the balance of As species. Liver and kidney were the accumulation and biotransformation sites, while shell was the main storage site. Moreover, compared with arsenite, arsenate was more prone to accumulate in the organs (intestine-stomach, head-foot, kidney, gonad, shell, heart, and hemolymph). Excretion through excrement is likely the primary mechanism contributing to the low accumulation of As and the subsequent rapid decline in As concentrations observed in various organs during the depuration period. Furthermore, our findings revealed a stimulating effect of As on the oviposition of P. canaliculata. Specifically, a concentration of 500 μg L−1 of arsenite in water significantly increased the oviposition rate by 36.88 %. These findings suggest a behavioral response and changes in reproductive patterns under As exposure. The increased egg production observed in response to As exposure provides insights into the adaptive mechanisms of this species in contaminated habitats.